What Works Best: A Systematic Review of Actual Learning in Marketing and Management Education Research. (April 2022) - Bacon, Donald R.; Stewart, Kim A.
After decades of research in marketing and management education, what do we now know about what educational practices work best for improving actual learning? We answer this question with a qualitative systematic literature review of every contribution published in five marketing and management education journals from inception through May 2020 that provides recommendations for evidence-based best pedagogical practice. Contributions were screened to identify empirical studies that employed measures of actual learning in an appropriate experimental design and reported analyses that met certain statistical standards. Of the 4, 160 articles examined, 55 studies met our criteria. Based on the studies' results, we developed a model for understanding the teaching methods that are most effective for achieving actual learning in marketing and management education. We provide evidence-based pedagogical recommendations for faculty and recommendations for additional research in key areas and for increasing the rigor of pedagogical research.